Lichen scrofulosorum in a 12-year-old girl: Role of dermoscopy and review of the literature. - Bhamidipati, H.S.; Singh, S.; Badabagni, P.; Mavoori, A.; Katike, P.; Gautam, A.; PVSVPHS, B. (European Journal of Pediatric Dermatology, 2024)
Lichen scrofulosorum (LS) is a rare tuberculosis resulting from a delayed hypersensitivity reaction to Mycobacterium tuberculosis. Dermoscopy of lichen scrofulosorum is little explored in the available literature. We report the dermoscopic findings of a 12-year-old girl who presented with multiple skin-colored follicular papules on the trunk and root of the limbs with a strongly positive Mantoux test. Based on clinical, histopathological and dermoscopic features, the diagnosis of lichen scrofulosorum was confirmed and the patient started antituberculosis therapy. To the best of our knowledge, only 5 similar cases of LS with dermoscopic evaluation are available in the literature. The present case highlighted the fundamental role of dermoscopy in the diagnosis of lichen scrofulosorum, particularly its ability to differentiate it from other follicular skin disorders.